2022
DOI: 10.1186/s12944-022-01674-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid profile with obesity among breast cancer survivors: a cross-sectional study

Abstract: Background The role of lipid metabolism in obesity and cancer manifestations cannot be underestimated, but whether alterations in lipid metabolism can manipulate the vasculature to promote obesity among breast cancer (BC) survivors is yet to be clearly understood. This study quantified plasma lipid and particle sizes using high-throughput proton (1H) nuclear magnetic resonance (NMR) and tested their associations with obesity among breast cancer (BC) survivors. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Regarding the correlations between BMI Index and lipids, this study revealed statistically positive correlations of BMI Index with pre-chemotherapy LDL-C, 1 st follow-up TC, 1 st follow-up LDL-C, 2 nd follow-up TC, and 2 nd follow-up LDL-C. This positive correlation was also highlighted by Okekunle et al (2022) [28] in their study among premenopausal women. The correlation between these variables is a less explored area and the mechanism behind this correlation is still unclear.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding the correlations between BMI Index and lipids, this study revealed statistically positive correlations of BMI Index with pre-chemotherapy LDL-C, 1 st follow-up TC, 1 st follow-up LDL-C, 2 nd follow-up TC, and 2 nd follow-up LDL-C. This positive correlation was also highlighted by Okekunle et al (2022) [28] in their study among premenopausal women. The correlation between these variables is a less explored area and the mechanism behind this correlation is still unclear.…”
Section: Discussionsupporting
confidence: 62%
“…The close relationship between HDL and ApoA-1 and BMI has been demonstrated in several studies, and a cross-sectional study involving 333 men found an inverse association between HDL and BMI (40). A recent cross-sectional study involving 348 patients reached the same conclusion (41). A meta-analysis study also pointed out that the increase of BMI was directly related to the decrease of ApoA-1 level (42).…”
Section: Discussionmentioning
confidence: 64%
“…Okekunle et al conducted a study that investigated the association between plasma lipids and obesity among breast cancer patients. The results indicated that increasing levels of serum TGs were associated with increasing body mass index among premenopausal breast cancer survivors (33).…”
Section: Frontiers Inmentioning
confidence: 89%